Theoretical and methodological foundations for the use of innovative simulators of locally directed impact during the training process of highly qualified armwrestling athletes - Kamayev, O.; Bezkorovainyi, D.; Mazurenko, I.; Vlasko, S.; Zvyagintseva, I. (Journal of Physical Education and Sport, 2020)
Purpose: A comparative analysis of strength indicators during the training process according to the experimental training program using innovative training equipment of locally directed action during the training of highly qualified armwrestling athletes. Material: The study involved 16 high qualification armwrestling athletes weighing between 80 and 100 kg. Group 1 - 8 (93.57 ± 0.94) kg, Group 2 - 8 (94.06 ± 0.95) kg. The athletes trained for one year: group 1 - according to the experimental program using innovative training equipment, group 2 - according to the traditional program. During the study, strength indicators were determined in 4 competitive exercises at the beginning and at the end of the experiment. Strength indices in all test exercises were measured in a static mode by an FB5k series electrical tenzodynamometer (Poland) with an accuracy class of up to 100 g, which was mounted on a special arm-sport table using a specially made block device. The created design was called the "ARM1 Device". During the statistical analysis, the following parameters were calculated: arithmetic mean (Cha ¯), standard deviation (B) (using Student t-test) and coefficient of variation (V), correlation analysis (using the Wilcoxon test). Results: A comparative analysis of the indicators of strength training among armwrestlers from the 1st and 2nd groups at the end of the study shows that their increase for the 1st group was more pronounced. Thus, an experimental training program using innovative locally directed simulators is more effective. This statement is confirmed by the dynamics of strength in all four test exercises with both left and right hands for athletes from the 1st group. An increase in strength training results ranged from 3.38% to 7.57%. The average increase was 5.06%. A comparison of the mean values by the nonparametric Wilcoxon criterion indicates that the difference between them is statistically significant (W = 2.52 ? W0.05 = 5). Conclusions: The performed analysis confirmed that the experimental training program was effective and allowed to significantly improve the strength indicators of highly qualified armwrestling athletes. This improvement occurred owing to the use of more time for static exercises by 46% and 70% for participating in competitions. Innovative local training equipment allowed to provide competitive movements without involving additional muscle groups. The experimental program, which used the innovative simulators of locally directed action, provided a significant development of the strength capabilities of those muscle groups that were directly involved in the fulfillment of certain strength motor actions.